Management of care for children/adolescents with chronic diseases: (dis)articulation of the network and fragmentation of the actions - Bruna Gabrielle de Araújo Silva; Amanda Narciso Machado; Vanessa Medeiros da Nóbrega; Renata Cardoso Oliveira; Elenice Maria Cecchetti Vaz; Neusa Collet (Universidade Federal de Santa Maria, 2020)
Objective: to analyze the management of care for children/adolescents with chronic diseases in the health care network, based on the experiences of families in the search for the care of their child. Method: a qualitative research, carried out with ten relatives of children/adolescents with chronic diseases, residents of the city of João Pessoa, Paraiba, Brazil. Data was collected from November 2017 to June 2018 through semi-structured interviews and submitted to inductive thematic analysis. Results: the health care network for children/adolescents with chronic diseases is disjointed and the care actions fragmented; families design their own therapeutic itineraries and do not receive support from e professionals/services in care management. Conclusion: disarticulation in the planning of care actions in health care networks, combined with punctual and discontinuous care for children/adolescents with chronic diseases and their family weaken and impoverish care management.